Evaluation of gender equity programme implementation in Limpopo Provincial Department of Sport, Arts and Culture - Nkoana, Nthabiseng Martha (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPA (Public Management and Planning))--University of Stellenbosch, 2010.